Pola Interaksi Sosial Keagamaan Antara Penganut Agama Islam Dan Kristen Advent (Studi Kasus di Desa Cihanjuang Rahayu Kecamatan Parongpong Kabupaten Bandung Barat) - Roro Sri Rejeki Waluyajati; Lia Ulfah Farida (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2018)
Interaction is a reciprocal relationship between the subject of the actor and who responds. This study aims to determine the background of the form of interaction as the actualization of religious teachings between adherents of Islam and Christian  Adventist. And to know its relevance to the understanding of the doctrine of religion that developed in the community. This research uses qualitative descriptive comparative method, while to obtain files, done using obeservation technique, interview and questionnaire. Based on the data obtained in this study, the background of the occurrence of a pattern of less harmonious interaction or simply said to be very minimal interaction on some Muslim society is due to the concerns of Christianization. The reason for avoiding various forms of interaction with non-Muslims conducted the community. In the larger group of adherents of Islam, engaging in social relations with Adventists does not become a problem for those relationships within the social sphere is a form of action that practices the teachings of scripture. Likewise in Christian Advent, for them to do social interaction that leads to unity and within the social sphere is an action in believing the Bible in everyday life. From that there are some activities that are built as structural villagers such as gotong royong, patrolling, work meetings, and social activities. Social activity is one activity that dominates the number of an interaction occurs between adherents of Islam and Christian Advent. Frequent social activities are free health services organized by Adventist Christians and used by Muslims.